2013
DOI: 10.4049/jimmunol.1301613
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Signaling through the G Protein–Coupled Estrogen Receptor Regulates Granulocyte Activation in Fish

Abstract: Neutrophils are major participants in innate host responses. It is well known that estrogens have an immune-modulatory role, and some evidence exists that neutrophil physiology can be altered by these molecules. Traditionally, estrogens act via classical nuclear estrogen receptors, but the identification of a G protein–coupled estrogen receptor (GPER), a membrane estrogen receptor that binds estradiol and other estrogens, has opened up the possibility of exploring additional estrogen-mediated effects. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 70 publications
(99 reference statements)
4
54
1
Order By: Relevance
“…We have previously reported that GPER1 signals via an adenylate cyclase/cAMP/PKA/CREB pathway in bony fish granulocytes [22]. It was found here that GPER1 not only uses a similar signaling pathway in human neutrophils, but also signals through p38 MAPK and ERK, as has been demonstrated in cancer cell lines [8,11,12,35].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…We have previously reported that GPER1 signals via an adenylate cyclase/cAMP/PKA/CREB pathway in bony fish granulocytes [22]. It was found here that GPER1 not only uses a similar signaling pathway in human neutrophils, but also signals through p38 MAPK and ERK, as has been demonstrated in cancer cell lines [8,11,12,35].…”
Section: Discussionsupporting
confidence: 75%
“…However, the activation induced by GPER1 signaling is not identical to the classical activation observed with LPS, since while both G1 and LPS stimulate CXCL8 release, G1 fails to induce the release of IL1RA . These observations contrast with the inability of GPER1 to consistently enhance the respiratory burst of bony fish granulocytes and its anti-inflammatory effect on these cells in which the sustained induction of genes encoding Ptgs2, prostaglandin D2 synthase, and IL-10 was observed upon G1 stimulation [22]. Moreover, G1 promotes a differential effect on neutrophil-respiratory burst compared to estrogens, which have been found to reduce superoxide anion release by human neutrophils [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…G-1 was also recently shown to modulate the respiratory burst in vertebrate granulocytes (neutrophils) as well as pro-and anti-inflammatory gene expression profiles (Cabas et al, 2013). A direct immunomodulatory function of G-1 in the endothelium was also demonstrated through attenuation of the tumor necrosis factor a-induced upregulation of proinflammatory adhesion molecules intercellular adhesion molecule-1 and vascular cell adhesion molecule-1 (Chakrabarti and Davidge, 2012).…”
Section: Immune Systemmentioning
confidence: 97%
“…mda5, melanoma differentiation-associated gene 5; lgp2, laboratory of genetics and physiology 2; mavs, mitochondrial antiviral signaling; traf3, tumor necrosis factor (TNF) receptor-associated factor 3; tank, TRAF3, family member-associated NF-kB activator 3; tbk1, TANK-binding kinase 1; irf, IFN regulatory factor; mx, myxovirus (influenza) resistance protein; pkr, dsRNA-dependent protein kinase receptor; er, estrogen receptor. Interestingly, ER activity has been shown to modulate innate immune signaling pathways in dendritic cells and macrophages in humans and fish [138][139][140][141]. The positive correlation observed between ERs and several molecules of the IFN pathway suggested that the modulation of the expression of ERs, together with the changes observed in the E 2 serum levels influence the ability of the immune system to react upon NNV infection.…”
Section: Nodavirus As a Viral Model To Unravel Fish Immuno-endocrine mentioning
confidence: 99%